Fungsi dan Nilai Nyanyian Buaian dalam Sastra Lisan Kaili - Afandi, Al (Bahasantodea, 2024)
This study was focused on the function and value of cradlesong in oral literature of Kailinese. This study aimed to describe the function and value incradle song. There are some of the concepts and theory used in this study,they are the theory of culture, folklore theory, the theory of functions of literature, and the theory of literary value. Method used in this study was a qualitative descriptive with naturalistic approach. Sources of data in this study obtained from informants in the field. Data is collecting by used direct observation, recording, interviews, and taking note (writing record). Analysis of data using interactive analysis with three stages of analysis, namely data reduction, data presentation, and inference. Cradle song collected and analyzed in this study were four poems that obtained from four different informants. Each of Informants who researched is an active user of cradle song in Dolo district. The results showed that the function of cradle song (mompaova) include (1) informational function, (2) educational function, (3) command function, and (4) the entertainment function. While the value contained in cradle song (mompaova) include (1) the moral values, (2) the philosophicalvalue, (3) the religious value, (4) the social values, and (5) the aesthetic value